PHYSICAL EDUCATION AS A PROFESSIONAL PRACTICE (Fiep Bulletin - online, 2013)
A Physical Education as practice. In this article we highlight aspects that involve the practice of physical educator, it can reflect the professional identity of this person and how to derive the construction of their professional identity. In this study we maintain a dialogue between the practice of physical education and physical educator, pointing elements considered relevant to the topic under study
Keywords: Physical Education; Physical Educator; professional Practice